2011
DOI: 10.3822/ijtmb.v4i1.118
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Massage on Pain, Stiffness, and Fatigue Levels Associated with Ankylosing Spondylitis: A Case Study

Abstract: Objectives:To study the effects of massage on pain, stiffness, and fatigue in a patient recently diagnosed with ankylosing spondylitis (AS).Methods: A 47-year-old woman with AS diagnosed 11 months earlier received 7 massages across a 28-day period. Her pain, stiffness, and fatigue were recorded using visual analogue scales daily during the study period. Spinal mobility was measured at each massage session with finger-to-floor measurements for both forward and lateral flexion. The client also used a daily journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The results also show that by using lumbar support, there was a higher comfort change in the upper back, lower back and buttock (Karuppiah et al, 2012). Besides, massage can reduce back pain, stiffness, and fatigue and could be used as a complement for the standard care of people (Chunco, 2011). The reduction in back pain is in line with Romanowski et al (2017) findings where they found that massage can reduce musculoskeletal disorders risks in a randomised clinical pilot study.…”
Section: Discomfort Ratingssupporting
confidence: 65%
“…The results also show that by using lumbar support, there was a higher comfort change in the upper back, lower back and buttock (Karuppiah et al, 2012). Besides, massage can reduce back pain, stiffness, and fatigue and could be used as a complement for the standard care of people (Chunco, 2011). The reduction in back pain is in line with Romanowski et al (2017) findings where they found that massage can reduce musculoskeletal disorders risks in a randomised clinical pilot study.…”
Section: Discomfort Ratingssupporting
confidence: 65%